Method for improving quality of chromium carbide product
By crushing and mixing the semi-finished chromium carbide products, combined with additives, molding and vacuum drying, and then sintering in a vacuum furnace, the problem of high impurity content of chromium carbide products in the prior art is solved, and high purity and low-cost preparation of chromium carbide is achieved.
Patent Information
- Application Number
- CN202411769830.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the impurity carbon content and other impurity content of chromium carbide products in the smelting of electric arc furnaces have high impurity content, resulting in low product value, high production cost, slow reaction rate, and difficult to meet commonly used market indicators.
By crushing the semi-finished chromium carbide into powder, mixing it with additives such as activated carbon and carbon black powder, it is uniformly mixed with a ball mill and a three-dimensional mixer, followed by molding and vacuum drying, and finally sintering in a vacuum furnace, and cooling is used to reduce the impurity content.
It improves the carbon content and purity of chromium carbide products, reduces the content of impurities, reduces production costs, is suitable for industrial production, and has a relatively simple process and stable product quality.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chromium carbide preparation, and more specifically, the invention relates to a method for improving the quality of chromium carbide products. Background Art
[0002] Chromium metal has high value due to its high corrosion resistance and hardness, but the semi-finished chromium carbide smelted in electric arc furnace has high impurity carbon content and low product value. As an important compound of chromium, chromium carbide has good wear resistance, corrosion resistance, and oxidation resistance under high temperature environment, and has a wide range of applications and higher product value. Therefore, it is of great significance to study the method of preparing chromium carbide from semi-finished chromium carbide smelted in electric arc furnace, which not only improves product value but also meets market demand.
[0003] At present, the production method of chromium carbide in China mainly adopts vacuum sintering to prepare chromium carbide. Regardless of whether metallic chromium or chromium oxide green is used as raw material, the reaction rate of carbon and chromium is slow and the production cost is too high. Due to the high viscosity of metallic chromium at high temperature and the large difference in density between carbon and chromium, chromium carbide segregation is prone to occur, resulting in uneven distribution of chromium carbide products, with some chromium carbides having high carbon content and some having low carbon content. In addition, high-temperature sintering will increase the carbon content of impurities and other impurities (Si, Fe, Al, P , S, etc.); for example, CN111484015A discloses a smelting method for chromium carbide, which uses electric arc smelting, and the impurity carbon content and other impurities of the prepared chromium carbide product are still high, and the carbon content of the prepared product does not meet the commonly used market indicators; another example is patent CN111439753A, which discloses a method for producing chromium carbide by smelting in an electric arc furnace, which uses chromium oxide as a raw material, has a slow smelting reaction rate, and a high smelting temperature, and the production cost is too high, and the carbon content of the prepared product does not meet the commonly used market indicators. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these objects and other advantages according to the present invention, a method for improving the quality of chromium carbide products is provided, comprising: Step 1, crushing the chromium carbide semi-finished product into chromium carbide semi-finished product powder; Step 2: The chromium carbide semi-finished product powder and the additive are mixed evenly by a ball mill, and then the obtained mixture and the binder are added into a three-dimensional mixer, and after mixing evenly, a molding device is used to press it into a honeycomb briquette-like block, and then it is dried in a vacuum drying oven; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. After sintering, introduce inert gas to cool the furnace to obtain chromium carbide.
[0006] Preferably, in the step 1, the chromium carbide semi-finished product produced by electric furnace smelting has C≥6wt% and Cr≥90wt%.
[0007] Preferably, in the step 1, the chromium carbide semi-finished product is crushed to a particle size of ≤200 mesh using a liquid nitrogen crusher.
[0008] Preferably, in step 2, the additive is one or a mixture of activated carbon, carbon black powder, graphite, coke, blue carbon and organic carbon, and the mass ratio of the chromium carbide semi-finished product powder to the additive is 20 to 40:3.
[0009] Preferably, in step 2, the binder is at least one of water, starch, phenolic resin, polyacrylamide, polyethylene glycol, polyvinyl alcohol, and cassava flour; and the mass ratio of the mixture to the binder is 90 to 330:3.
[0010] Preferably, in the step 2, the mixing time in the three-dimensional mixer is 20 to 180 minutes, the pressure parameter of the compression molding is 10 to 40 MPa, the drying temperature is 50 to 100° C., and the drying time is 3 to 6 hours.
[0011] Preferably, in step 2, the honeycomb briquettes have a diameter of 15 to 30 cm and a height of 15 to 20 cm, and are evenly distributed with circular air-permeable channels with a diameter of 8 to 12 mm.
[0012] Preferably, in step three, the vacuum sintering parameters are vacuum degree ≤ 500 Pa, temperature 1000-1600° C., and insulation time 10-50 h.
[0013] Preferably, in step 3, when the furnace is cooled down, after the temperature drops to 200° C., an inert gas is introduced to the room temperature, and the product is taken out of the furnace to obtain chromium carbide, and the inert gas is argon or helium.
[0014] Preferably, after step 3, the obtained chromium carbide may be crushed to a desired particle size.
[0015] The present invention has at least the following beneficial effects: (1) The present invention uses a ball mill to grind and mix the high-carbon metallic chromium produced by the electric furnace smelting method, so that the semi-finished chromium carbide powder and the additive are mixed more evenly, the contact area of the mixture is increased, and it is more conducive to the reaction. Then, a three-dimensional mixer is used to mix the powder and the binder. The three-dimensional effect can effectively improve the mixing efficiency and prevent the material from agglomerating. (2) The present invention uses a mixture of one or more of activated carbon, carbon black powder, graphite, coke, blue carbon and organic carbon as an additive to carry out a high-temperature reduction reaction in a vacuum furnace, converting the carbon in the additive into chromium carbide to increase the carbon content of the product; the vacuum condition is used to reduce the reaction temperature, and the impurity elements of the obtained product are extremely low, which reduces the cost of raw materials and process, has little pollution to the environment, and is suitable for industrial production; the present invention mixes the mixture with a binder and presses it into a honeycomb briquette-like block, which can efficiently guide the gas generated in the reaction and be extracted under a vacuum environment, thereby improving the reaction efficiency; Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION The present invention is described in further detail below so that those skilled in the art can implement it according to the description.
[0017] Example 1 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 91.85%) into a ball mill, add 0.8 kg of carbon black powder, and mill at a speed of 300 r / min for 30 min to obtain a mixture. Add the mixture and starch into a three-dimensional mixer at a mass ratio of 200:3, mix for 30 min, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block. The pressure parameter is 25 MPa. The honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm. Circular air permeable channels with a diameter of 10 mm are evenly distributed on it, and then dried in a vacuum drying oven at 50 ° C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 500Pa, temperature 1300°C, and insulation for 12 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0018] Example 2 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 91.44%) into a ball mill, then add 0.796 kg of carbon black powder, and ball mill at a speed of 300 r / min for 30 min to obtain a mixture, add the mixture and starch into a three-dimensional mixer at a mass ratio of 100:3, mix for 30 min, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block, the pressure parameter is 25 MPa, the honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm, and circular air permeable channels with a diameter of 10 mm are evenly distributed thereon, and then dried in a vacuum drying oven at 50 ° C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 300Pa, temperature 1200°C, and insulation for 12 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0019] Example 3 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 91.59%) into a ball mill, add 0.86 kg of activated carbon powder, and mill at a speed of 300 r / min for 30 min to obtain a mixture. Add the mixture and starch into a three-dimensional mixer at a mass ratio of 290:3, mix for 30 min, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block. The pressure parameter is 30 MPa. The honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm. Circular air permeable channels with a diameter of 10 mm are evenly distributed on it, and then dried in a vacuum drying oven at 50 ° C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 400Pa, temperature 1200°C, and insulation for 20 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0020] Example 4 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 92.64%) into a ball mill, add 0.81 kg of graphite carbon powder, and mill at a speed of 300 r / min for 30 min to obtain a mixture. Add the mixture and starch into a three-dimensional mixer at a mass ratio of 100:3, mix for 30 min, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block. The pressure parameter is 25 MPa. The honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm. Circular air permeable channels with a diameter of 10 mm are evenly distributed thereon, and then dried in a vacuum drying oven at 50 ° C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 500Pa, temperature 1300°C, and insulation for 28 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0021] Comparative Example 1 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 91.85%) into a ball mill, add 0.8 kg of carbon black powder, and mill at a speed of 300 r / min for 30 min to obtain a mixture. Add the mixture and starch into a non-three-dimensional mixer at a mass ratio of 200:3, mix for 30 min, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block. The pressure parameter is 25 MPa. The honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm. Circular air permeable channels with a diameter of 10 mm are evenly distributed on it, and then dried in a vacuum drying oven at 50 ° C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 500Pa, temperature 1300°C, and insulation for 12 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0022] Comparative Example 2 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 0.8 kg of carbon black powder to 10 kg of chromium carbide semi-finished powder (Cr content of 91.85%) to obtain a mixture, add the mixture and starch into a three-dimensional mixer at a mass ratio of 200:3, mix for 30 minutes, and after mixing evenly, use a compression molding device to press it into a honeycomb briquette-like block. The pressure parameter is 25 MPa. The honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm. Circular air permeable channels with a diameter of 10 mm are evenly distributed thereon, and then dried in a vacuum drying oven at 50°C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 500Pa, temperature 1300°C, and insulation for 12 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0023] Comparative Example 3 A method for improving the quality of chromium carbide products comprises the following steps: Step 1, crushing the chromium carbide semi-finished product produced by the electric furnace smelting method into a pretreatment bin of a liquid nitrogen pulverizer, and pulverizing the semi-finished chromium carbide powder with a particle size of 200 mesh; Step 2: Add 10 kg of chromium carbide semi-finished powder (Cr content of 91.85%) into a ball mill, then add 0.8 kg of carbon black powder, and ball mill at a speed of 300 r / min for 30 minutes to obtain a mixture, add the mixture into a three-dimensional mixer, mix for 30 minutes, and after mixing evenly, use a molding device to press it into a honeycomb briquette-like block, the pressure parameter is 25 MPa, the honeycomb briquette-like block has a diameter of 25 cm and a height of 18 cm, and circular air permeable channels with a diameter of 10 mm are evenly distributed thereon, and then dried in a vacuum drying oven at 50°C; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. The sintering parameters are vacuum degree 500Pa, temperature 1300°C, and insulation for 12 hours. After sintering, cool the furnace to 200°C, then introduce helium to continue cooling to room temperature to obtain chromium carbide.
[0024] Comparative Example 4 The difference between this comparative example and Example 1 is that no carbon black powder is added in step 2, and the rest is consistent with Example 1.
[0025] The chromium carbide products obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were tested for component content. The test results are shown in Table 1 below, and reference is made to the commonly used market indicators in Table 2 to determine whether they meet the standards.
[0026] Table 1 Table 2 It can be seen from Table 1 that the contents of each component in Examples 1 to 4 are in accordance with the index requirements in Table 2, and the impurity content is far lower than the index requirements. In addition, the chromium carbide product prepared by the present invention has high purity and stable quality, and the process flow is simple.
[0027] In Comparative Example 1, since a three-dimensional mixer was not used to mix the powder and the adhesive, the stirring efficiency was low and the mixing was not uniform, resulting in a lower carbon content in the product than in Examples 1-4, and Comparative Example 1 was only slightly higher than the commonly used market indicators, which may be caused by testing errors and is also considered not to meet market indicators; in Comparative Example 2, a ball mill was not used for grinding and mixing, and the metal chromium powder and the additive were not mixed uniformly, resulting in lower Cr and C contents in the product than in Examples 1-4, and Comparative Example 2 was only slightly higher than the commonly used market indicators, which may be caused by testing errors and is also considered not to meet market indicators; in Comparative Example 3, no adhesive was used, and the metal chromium powder and the additive were not tightly combined, resulting in poor molding effect, resulting in the carbon content of the product being too low to meet the indicator requirements; in Comparative Example 4, no additives were added and no carbon was introduced to increase the carbon content, resulting in the carbon content of the product being far lower than the market indicators. At the same time, the impurity contents of the products prepared in Comparative Examples 1-4 were higher than those in Examples 1-4.
[0028] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for improving the quality of chromium carbide products, characterized in that: include: Step 1, crushing the chromium carbide semi-finished product into chromium carbide semi-finished product powder; Step 2: The chromium carbide semi-finished product powder and the additive are mixed evenly by a ball mill, and then the obtained mixture and the binder are added into a three-dimensional mixer, and after mixing evenly, a molding device is used to press it into a honeycomb briquette-like block, and then it is dried in a vacuum drying oven; Step 3: Place the dried honeycomb briquettes into a vacuum furnace for sintering. After sintering, introduce inert gas to cool the furnace to obtain chromium carbide.
2. A method for improving the quality of chromium carbide products according to claim 1, characterized in that: In the step 1, C≥6wt% and Cr≥90wt% in the chromium carbide semi-finished product.
3. A method for improving the quality of chromium carbide products according to claim 1, characterized in that: In the step 1, the semi-finished chromium carbide is crushed to a particle size of ≤200 mesh using a liquid nitrogen crusher.
4. A method for improving the quality of chromium carbide products according to claim 1, characterized in that: In the step 2, the additive is one or a mixture of activated carbon, carbon black powder, graphite, coke, blue carbon and organic carbon, and the mass ratio of the chromium carbide semi-finished product powder to the additive is 20 to 40:
3.
5. A method for improving the quality of chromium carbide products according to claim 1, characterized in that: In the step 2, the binder is at least one of water, starch, phenolic resin, polyacrylamide, polyethylene glycol, polyvinyl alcohol, and cassava flour; and the mass ratio of the mixture to the binder is 90 to 330:
3.
6. A method for improving the quality of chromium carbide products as claimed in claim 1, characterized in that: In the step 2, the mixing time in the three-dimensional mixer is 20 to 180 minutes, the pressure parameter of the compression molding is 10 to 40 MPa, the drying temperature is 50 to 100° C., and the drying time is 3 to 6 hours.
7. A method for improving the quality of chromium carbide products as claimed in claim 1, characterized in that: In the step 2, the honeycomb briquettes have a diameter of 15 to 30 cm and a height of 15 to 20 cm, and are evenly distributed with circular air-permeable channels with a diameter of 8 to 12 mm.
8. A method for improving the quality of chromium carbide products as claimed in claim 1, characterized in that: In the step three, the vacuum sintering parameters are vacuum degree ≤ 500 Pa, temperature 1000-1600° C., and heat preservation for 10-50 hours.
9. A method for improving the quality of chromium carbide products as claimed in claim 1, characterized in that: In the step 3, when the furnace is cooled down, after the temperature drops to 200° C., an inert gas is introduced to the room temperature, and the furnace is taken out to obtain chromium carbide, wherein the inert gas is argon or helium.
10. A method for improving the quality of chromium carbide products according to claim 1, characterized in that: After step 3, the obtained chromium carbide may be crushed to a desired particle size.
Citation Information
Patent Citations
Smelting method of chromium carbide
CN111484015A